The feasibility of conducting compressed air energy storage system - Feng Yucheng (E3S Web of Conferences)
Energy storage has been a crucial component in human energy utilization, with the compressed air energy storage system (CAES) emerging as a significant and indispensable aspect of the conversation around energy storage solutions. Historically, the understanding of CAES was confined to theoretical models, but recent years have witnessed an increase in practical applications and constructions, bringing the technology into the public eye. These developments have yielded valuable and precise data that researchers can leverage. Utilizing these data points, this paper employs both qualitative and quantitative analysis to thoroughly evaluate the viability of implementing CAES systems. The aim of this article is to provide some insights that can significantly contribute to the advancement of CAES technology, offering a comprehensive assessment that informs future development strategies. Furthermore, the difficulty of the technology is analyzed and some solutions are provided. Finally, the further development trend of compressed air energy storage system is conducted.